Negative pole piece and battery with same
By using porous current collector and carbon material layer in the negative electrode sheet of the negative electrode without the negative electrode, the lithium dendrites problem is solved, and the safety performance and energy density of the battery are improved.
Patent Information
- Application Number
- CN202420324574.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Utility models(China)
- Current Assignee / Owner
- Filing Date
- 2024-02-21
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2034-02-21
AI Technical Summary
There is a lithium dendrite problem in negative electrode lithium batteries, resulting in deterioration of battery performance and safety hazards.
A negative electrode sheet is designed, including a porous current collector and a carbon material layer disposed on its surface. The porosity of the carbon material layer is 20% to 70%, and the porosity of the porous current collector is 10% to 90%, so as to increase the deposition site of lithium ions and reduce the length of lithium dendrites.
By increasing the deposition site of lithium ions, the length of lithium dendrites is reduced, and the safety performance and energy density of the battery are improved.
Smart Images

Figure CN222637301U_ABST
Abstract
Description
Technical Field
[0001] The utility model relates to the technical field of batteries, and in particular to a negative electrode sheet and a battery having the same. Background Art
[0002] In recent years, in order to achieve lithium metal batteries with higher energy density, lithium metal-free anode-free lithium batteries represent one of the most advanced technologies in the field of lithium batteries. Although anode-free cells will increase the energy density of the cells, anode-free cells also have the problem of lithium dendrites. For example, lithium dendrites are easily formed during the lithium deposition / stripping process. Uncontrollable lithium dendrite growth will pierce the diaphragm, deteriorate performance, and cause battery short circuit and thermal runaway, causing safety problems. In other words, due to the existence of lithium dendrite problems, it is easy to cause safety hazards in the battery cells. Therefore, it is necessary to develop effective solutions to alleviate the problem of lithium dendrites and thus improve the safety performance of the battery.
[0003] In view of this, the present utility model is proposed. Utility Model Content
[0004] In view of this, the utility model aims to solve one of the technical problems in the related art to at least a certain extent. To this end, the utility model provides a negative electrode plate and a battery having the same, which can reduce the length of lithium dendrites and improve the safety performance of the battery.
[0005] In order to solve the above technical problems, this application is implemented as follows:
[0006] According to one aspect of the present application, an embodiment of the present application provides a negative electrode plate, the negative electrode plate comprising:
[0007] porous current collector;
[0008] a carbon material layer, the carbon material layer being disposed on at least one surface of the porous current collector in a thickness direction;
[0009] Wherein, the porosity of the carbon material layer is 20% to 70%, and the porosity of the porous current collector is 10% to 90%.
[0010] In addition, the negative electrode sheet according to the present application may also have the following additional technical features:
[0011] In some embodiments, the porous current collector includes one of copper foam or modified copper foam.
[0012] In some embodiments, the pore size of the porous current collector is 0.05 mm to 5 mm;
[0013] The thickness of the porous current collector is 5 μm to 50 μm.
[0014] In some embodiments, the carbon material layer is a porous carbon layer, and the porous carbon layer is any one of carbon nanospheres, carbon nanotubes, carbon nanosheets, or three-dimensional nanocarbon materials;
[0015] The pores of the porous carbon layer have a pore size of 0.6 nm to 4 nm.
[0016] In some embodiments, the carbon material layer is a common carbon material layer, and the common carbon material layer is any one of graphene, conductive carbon black, activated carbon or carbon nanotubes.
[0017] In some embodiments, the carbon material layer has a thickness of 1 μm to 10 μm.
[0018] In some embodiments, the negative electrode plate further includes a non-conductive protective layer, and the non-conductive protective layer is disposed on a surface of the carbon material layer that is away from the porous current collector.
[0019] In some embodiments, the thickness of the non-conductive protective layer is 1 μm to 10 μm.
[0020] In some of the embodiments, the non-conductive protective layer is a ceramic layer or a silicon material layer;
[0021] Wherein, the ceramic layer is any one of aluminum oxide, boehmite, zirconium oxide, magnesium zirconium oxide, silicon oxide or silicon nitride;
[0022] The particle size of the ceramic in the ceramic layer is 2 μm to 7 μm;
[0023] The silicon material layer is any one of silicon single substance, silicon alloy, silicon oxygen material or silicon nitrogen material.
[0024] According to another aspect of the present application, an embodiment of the present application provides a battery, the battery comprising:
[0025] A positive electrode sheet, a negative electrode sheet as described above, and an electrolyte.
[0026] The implementation of the technical solution of the utility model has at least the following beneficial effects:
[0027] In an embodiment of the present application, the provided negative electrode plate is suitable for a negative electrode-free battery, and the negative electrode plate includes a porous current collector and a carbon material layer arranged on at least one surface of the porous current collector, wherein the porosity of the porous current collector is 10% to 90%, and the porosity of the carbon material layer is 20% to 70%. Thus, by making the porosity of the porous current collector and the carbon material layer within the above range, the porosity of the negative electrode plate is increased, and the pores in the porous current collector and the carbon material layer can provide space for the deposition of active ions such as lithium ions, thereby reducing the deposition of active ions such as lithium ions on the surface of the current collector, thereby reducing the length of lithium dendrites, improving the safety performance of the battery, and providing certain protection for lithium dendrites, thereby improving the safety performance of the battery.
[0028] Additional aspects and advantages of the present application will be given in part in the following description, and in part will become apparent from the following description, or will be understood through the practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] The above and other purposes, features and advantages of the present invention will become more apparent by describing the embodiments of the present invention in more detail in conjunction with the accompanying drawings. The accompanying drawings are used to provide a further understanding of the embodiments of the present invention and constitute a part of the specification. Together with the embodiments of the present invention, they are used to explain the present invention and do not constitute a limitation of the present invention. In the accompanying drawings, the same reference numerals generally represent the same components or steps.
[0030] Figure 1 The figure shows a schematic diagram of the structure of a negative electrode sheet provided by an embodiment of the utility model;
[0031] Figure 2 The figure shows a schematic diagram of the structure of a porous current collector provided by an embodiment of the utility model;
[0032] Figure 3 Shown is a schematic structural diagram of another negative electrode sheet provided in an embodiment of the utility model.
[0033] Description of reference numerals:
[0034] 10-porous current collector; 110-hole;
[0035] 20-carbon material layer;
[0036] 30-Non-conductive protective layer. DETAILED DESCRIPTION
[0037] The present application is further described below in conjunction with specific embodiments. It should be understood that these embodiments of the present application are only used to illustrate the present application and are not used to limit the scope of the present application.
[0038] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range or the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0039] Below, the embodiments of the negative electrode plate, battery, etc. of the present application are specifically disclosed with appropriate reference to the drawings. However, there may be cases where unnecessary detailed descriptions are omitted. For example, there are cases where detailed descriptions of well-known matters and repeated descriptions of actually the same structure are omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate the understanding of those skilled in the art. In addition, the drawings and the following descriptions are provided for those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.
[0040] If there is no special description, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution. If there is no special description, all technical features and optional technical features of the present application can be combined with each other to form a new technical solution.
[0041] The embodiments of the present application are described in detail below through specific embodiments and their application scenarios in conjunction with the accompanying drawings.
[0042] Negative electrode-free batteries usually refer to batteries without negative electrode active materials. Negative electrode-free batteries can improve the energy density of batteries by not using negative electrode active materials. The technical principle of negative electrode-free batteries is to deposit the lithium in the positive electrode on the negative electrode current collector through formation charging or during the first charging of the battery. However, the interaction between the negative electrode structure or the negative electrode current collector and lithium in the related technology is weak, resulting in uneven lithium deposition. Uncontrollable lithium deposition will form dendrites, deteriorate performance, and cause safety hazards. In other words, the existing negative electrode-free batteries mainly have the problem of lithium dendrites, which leads to safety hazards in the batteries.
[0043] In view of this, the technical solution of the embodiment of the present application provides an improved negative electrode plate, which can be a negative electrode plate without negative electrode active material, and the negative electrode plate can be used in a negative electrode-free battery. The technical solution of the embodiment of the present application can alleviate the problem of lithium dendrites in existing negative electrode-free batteries, thereby reducing the length of lithium dendrites, providing protection for lithium dendrites, and improving the energy density and safety performance of negative electrode-free batteries. The description of the specific technical solution is as follows.
[0044] See also Figures 1 to 3As shown, an embodiment of the present application provides a negative electrode plate, which includes: a porous current collector 10 and a carbon material layer 20;
[0045] The carbon material layer 20 is disposed on at least one surface of the porous current collector 10 in the thickness direction;
[0046] The porosity of the carbon material layer 20 is 20% to 70%, and the porosity of the porous current collector 10 is 10% to 90%.
[0047] The above “the carbon material layer is disposed on at least one surface of the porous current collector along the thickness direction” means that the carbon material layer can be disposed on one surface of the porous current collector along its own thickness direction, or on two surfaces of the porous current collector along its own thickness direction. The “surface” here can be the entire area of the porous current collector or a partial area of the porous current collector. This application has no particular limitation, as long as the purpose of this application can be achieved.
[0048] Optionally, in this embodiment, the porous current collector 10 has two surfaces opposite to each other in its thickness direction, and the carbon material layer 20 is disposed on the two opposite surfaces of the porous current collector 10. It is understood that, in other embodiments, the carbon material layer 20 may also be stacked on any one of the two surfaces of the porous current collector 10.
[0049] The porosity of the carbon material layer 20 is 20% to 70%. When the porosity of the carbon material layer 20 is within the above range, it helps to provide sufficient lithium ion deposition sites, optimize the deposition of lithium ions inside the porous current collector, and thus reduce the deposition of lithium ions on the surface of the porous current collector. In addition, when the porosity of the carbon material layer 20 is within the above range, lithium ions can be deposited in the pores of the carbon material layer 20, reducing the deposition and formation of lithium dendrites on the surface and improving the safety performance of the battery; at the same time, when the porosity of the carbon material layer 20 is within the above range, it can reduce the impact on the energy density of the battery cell, that is, it helps to improve the energy density of the battery cell. In addition, when the porosity of the carbon material layer 20 is within the above range, the carbon material layer 20 can also absorb the electrolyte, thereby improving the liquid retention of the battery cell, thereby reducing the deposition of lithium ions on the surface of the electrode due to the lack of electrolyte. Illustratively, the porosity of the carbon material layer 20 may be 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70%, or a range consisting of any two of the above values.
[0050] The porosity of the porous current collector 10 is 10% to 90%. When the porosity of the porous current collector 10 is within the above range, the pores in the porous current collector 10 can be used as a space for lithium deposition, and can provide sufficient lithium ion deposition sites, which can reduce or avoid the deposition of lithium dendrites on the surface, thereby reducing the length of lithium dendrites or eliminating lithium dendrites, and improving the safety performance of the battery; at the same time, when the porosity of the porous current collector 10 is within the above range, it can reduce the impact on the energy density of the battery cell, that is, it helps to improve the energy density of the battery cell. Exemplarily, the porosity of the porous current collector 10 can be 10%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75%, 80%, 90%, or a range consisting of any two of the above values.
[0051] In addition, by making the porosity of the carbon material layer 20 and the porous current collector 10 within the above-mentioned range, it can be ensured that there are enough through holes on the carbon material layer 20 and the porous current collector 10 to provide enough lithium ion deposition sites, and it can also be ensured that the carbon material layer 20 and the porous current collector 10 have the strength to meet actual needs.
[0052] It should be explained that in the embodiments of the present application, porosity has a well-known meaning in the art and can be tested using methods and instruments known in the art. Usually, the porosity of a porous current collector refers to the ratio of the volume of all pores in the porous current collector to the total volume of the porous current collector; similarly, the porosity of a carbon material layer refers to the ratio of the volume of all pores in the carbon material layer to the total volume of the carbon material layer. In the embodiments of the present application, the porosity of the porous current collector and the carbon material layer can be monitored by a charge-coupled device (CCD); alternatively, the porosity can be measured by a gas displacement method in accordance with GB / T24586.
[0053] Therefore, based on the above settings, by setting a carbon material layer 20 on the surface of the porous current collector 10, and making the porosity of the porous current collector 10 and the carbon material layer 20 respectively satisfy the above ranges, the deposition sites of lithium ions inside the porous current collector 10 can be increased, thereby increasing the deposition of lithium ions inside the porous current collector 10 such as foam copper; reducing the deposition of lithium ions on the surface of the porous current collector 10 such as the copper current collector, thereby reducing the length of lithium dendrites and improving the safety performance of the battery.
[0054] The pores in the provided porous current collector 10 and the carbon material layer 20 can provide space for the deposition of lithium ions, reduce the deposition of lithium ions on the surface of the current collector, thereby reducing the length of lithium dendrites and improving the safety performance of the battery.
[0055] The pores in the carbon material layer 20 can also absorb the electrolyte, thereby improving the electrolyte retention of the battery.
[0056] A carbon material layer 20 having a certain thickness is arranged on the surface of the porous current collector 10 to provide certain protection for lithium dendrites on the surface of the current collector.
[0057] A carbon material layer 20 is disposed on the surface of the porous current collector 10. Since the carbon material layer 20 has certain electrical conductivity, the electrical conductivity of the current collector can also be improved.
[0058] In some embodiments, the porosity of the carbon material layer 20 is 25% to 60%. In some embodiments, the porosity of the carbon material layer 20 is 30% to 50%.
[0059] In some embodiments, the porosity of the porous current collector 10 is 20% to 80%. In some embodiments, the porosity of the porous current collector 10 is 30% to 70%.
[0060] By further optimizing the porosity range of the carbon material layer 20 and the porous current collector 10, it is helpful to further increase the deposition sites for lithium ions, further optimize the deposition of lithium ions inside the porous current collector 10, and thereby reduce the length of lithium dendrites or eliminate lithium dendrites; it is also helpful to improve the energy density of the battery while maintaining the strength that meets actual requirements.
[0061] In some embodiments, the porous current collector 10 includes one of copper foam or modified copper foam.
[0062] Optionally, in some embodiments, the porous current collector 10 is foamed copper.
[0063] Optionally, in some other embodiments, the porous current collector 10 is a modified copper foam. The modified copper foam can be a modified copper foam having a porous structure obtained by modifying copper foam in any modification method in the prior art. This embodiment does not limit the modification method of the modified copper foam, and any modified copper foam known in the prior art can be used.
[0064] In addition, in other embodiments, the specific types of the porous current collector 10 are not limited to the above types. Under the conditions of meeting the requirements of increasing the deposition sites of lithium ions inside the porous current collector 10 and reducing the length of lithium dendrites, the porous current collector 10 can also adopt other current collectors with porous structures such as foamed nickel, foamed aluminum, etc., which are not listed one by one here.
[0065] In this embodiment, when copper foam or modified copper foam is used as the current collector of the negative electrode-free battery, the pores or voids of the copper foam or modified copper foam can be used as a space for lithium deposition, thereby reducing or avoiding the deposition of lithium dendrites on the surface, thereby reducing the length of lithium dendrites or eliminating lithium dendrites. On the other hand, since there is usually a layer of copper oxide on the surface of copper foam or modified copper foam, which affects the conductivity of the surface of copper foam, the present application provides a carbon material layer 20 on the internal pore surface and the outer surface of the copper foam or modified copper foam, such as depositing a conductive porous carbon layer by vapor deposition, which can increase the deposition site of lithium ions on the surface of copper foam or modified copper foam, thereby optimizing the deposition of lithium ions inside the copper foam or modified copper foam, thereby reducing the deposition of lithium ions on the surface of copper foam or modified copper foam. Further, the interior of the carbon material layer 20 is porous, and lithium ions can be deposited in the pores, reducing the deposition and formation of lithium dendrites on the surface. In addition, the carbon material layer 20 can absorb electrolyte, thereby improving the liquid retention of the battery cell, and further reducing the deposition of lithium ions on the surface of the electrode due to lack of electrolyte. In addition, the carbon material layer 20 provided on the surface of the copper foam or modified copper foam has a certain thickness, which can provide certain protection for lithium dendrites on the surface of the current collector.
[0066] In some embodiments, the thickness of the porous current collector 10 is 5 μm to 50 μm. Optionally, in some embodiments, the thickness of the porous current collector 10 is 10 μm to 40 μm. Optionally, in some embodiments, the thickness of the porous current collector 10 is 15 μm to 35 μm. Exemplarily, the thickness of the porous current collector 10 can be 5 μm, 6 μm, 8 μm, 10 μm, 15 μm, 20 μm, 25 μm, 30 μm, 35 μm, 40 μm, 50 μm, or a range consisting of any two of the above values.
[0067] By making the thickness of the porous current collector within the above range, it is beneficial to manufacture a thin and light negative electrode sheet, thereby improving the energy density of the battery cell, and it is also helpful to provide sufficient lithium ion deposition sites, reduce the length of lithium dendrites, or inhibit the formation of lithium dendrites, and improve safety performance. At the same time, by making the thickness of the porous current collector within the above range, it is possible to avoid the problem of prolonged preparation process time and increased cost caused by excessive thickness of the porous current collector, and it is also possible to avoid the problem of reduced conductivity and strength caused by excessive thin thickness of the porous current collector, thereby affecting the conductivity and strength of the negative electrode sheet.
[0068] In some embodiments, the thickness of the carbon material layer 20 is 1 μm to 10 μm. Optionally, in some embodiments, the thickness of the carbon material layer 20 is 1 μm to 8 μm. Optionally, in some embodiments, the thickness of the carbon material layer 20 is 1 μm to 5 μm. Exemplarily, the thickness of the carbon material layer 20 can be 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, or a range consisting of any two of the above values.
[0069] By making the thickness of the carbon material layer 20 within the above range, it is beneficial to manufacture a thin and light negative electrode plate, thereby improving the energy density of the battery cell, and also helps to provide sufficient lithium ion deposition sites, reduce the length of lithium dendrites, or inhibit the formation of lithium dendrites, thereby improving safety performance. In addition, by making the thickness of the carbon material layer 20 within the above range, it is also possible to provide a certain degree of protection for the lithium dendrites on the surface of the current collector, thereby avoiding the problems of increased cost, reduced protection performance, or reduced conductivity caused by the carbon material layer 20 being too thick or too thin.
[0070] In some embodiments, the pore size of the pores 110 of the porous current collector 10 is 0.05 mm to 5 mm. Optionally, in some embodiments, the pore size of the pores 110 of the porous current collector 10 is 0.05 mm to 3 mm. Optionally, in some embodiments, the pore size of the pores 110 of the porous current collector 10 is 0.05 mm to 1 mm. Exemplarily, the pore size of the pores 110 of the porous current collector 10 can be 0.05 mm, 0.06 mm, 0.07 mm, 0.08 mm, 0.09 mm, 0.1 mm, 0.2 mm, 0.4 mm, 0.5 mm, 1 mm, 2 mm, 3 mm, 4 mm, 5 mm, or a range consisting of any two of the above values.
[0071] The porous current collector 10 may have a plurality of holes 110, the shapes of the plurality of holes 110 may be the same or different, the plurality of holes 110 may be regular or irregular holes, the plurality of holes may be arranged in parallel and / or crosswise, etc., and the present embodiment does not limit the specific arrangement of the holes 110 in the porous current collector 10. The composition of the porous structure includes pore size, pore length, pore size distribution, etc. The pore size may be micropores, mesopores, or macropores, etc., and micropores, mesopores, and macropores are pores with gradually increasing pore sizes.
[0072] In the embodiment of the present application, the pore size of the pores 110 of the porous current collector 10 is in the range of 0.05 mm to 5 mm, especially in the range of 0.05 mm to 0.1 mm. On the one hand, it is beneficial to improve the structural strength of the porous current collector 10, and on the other hand, it is beneficial to the deposition of lithium ions, and dead lithium caused by excessive pore size of the porous structure can be avoided.
[0073] In the present application, the carbon material layer 20 can be made of porous carbon or ordinary carbon material, as long as the porosity of the formed carbon material layer 20 is within the range of 20% to 70%, which can not only improve the conductivity of the current collector, but also facilitate the deposition of lithium ions.
[0074] In some embodiments, the carbon material layer 20 is a porous carbon layer, and the porous carbon layer is any one of carbon nanospheres, carbon nanotubes, carbon nanosheets, or three-dimensional nanocarbon materials. For example, the porous carbon layer can be a carbon nanosphere layer, a carbon nanotube layer, a carbon nanosheet layer, a three-dimensional nanocarbon material layer 20, etc. Of course, in other embodiments, any other known porous carbon material with a porous structure can also be used. The above-mentioned carbon nanospheres, carbon nanotubes, carbon nanosheets, or three-dimensional nanocarbon materials are all materials known in the prior art, and this embodiment does not limit their sources.
[0075] In some embodiments, the pores of the porous carbon layer have a pore size of 0.6nm to 4nm. Optionally, in some embodiments, the pores of the porous carbon layer have a pore size of 0.8nm to 3nm. Optionally, in some embodiments, the pores of the porous carbon layer have a pore size of 1.0nm to 2.5nm. Exemplarily, the pore size of the pores of the porous carbon layer can be 0.6nm, 0.8nm, 1nm, 1.5nm, 2nm, 2.5nm, 3nm, 4nm, or a range consisting of any two of the above values.
[0076] The porous carbon layer may have a plurality of pores, and the plurality of pores may be arranged in parallel and / or crosswise, etc. The present embodiment does not limit the specific arrangement of the pores in the porous carbon layer. The composition of the porous structure includes pore diameter, pore length, pore diameter distribution, etc. The pore diameter may be micropore, mesopore, or macropore, etc. Micropore, mesopore, and macropore are pores with gradually increasing pore diameters.
[0077] In the embodiment of the present application, the pores in the porous carbon layer can be nanoscale pores, especially the pores of the porous carbon layer have a pore size in the range of 0.6nm to 4nm. On the one hand, it is beneficial to improve the deposition of lithium ions and reduce the length of lithium dendrites. On the other hand, it is beneficial to improve the structural strength of the porous carbon layer.
[0078] In other embodiments, the carbon material layer 20 is a common carbon material layer, and the common carbon material layer is any one of graphene, conductive carbon black, activated carbon or carbon nanotubes. For example, the common carbon material layer can be a graphene layer, a conductive carbon black layer, an activated carbon layer, a carbon nanotube layer, etc.; of course, in other embodiments, any other known common carbon material can also be used. The above-mentioned graphene, conductive carbon black, activated carbon, and carbon nanotubes are all materials known in the prior art, and this embodiment does not limit their sources.
[0079] Optionally, in some embodiments, the carbon material layer 20 may be a vapor-deposited carbon material layer, that is, the carbon material is deposited on the surface of the porous current collector 10 by vapor deposition, thereby forming the carbon material layer 20 on the surface of the porous current collector 10 .
[0080] Optionally, in some implementations, a small amount of binder may be provided in the carbon material layer 20 , and this embodiment does not limit the specific type of the binder.
[0081] In order to further provide certain protection for lithium dendrites, thereby further improving the safety performance of the battery, the negative electrode plate of this embodiment is also provided with a non-conductive protective layer 30. In some embodiments, the negative electrode plate also includes a non-conductive protective layer 30, and the non-conductive protective layer 30 is arranged on the surface of the carbon material layer 20 on the side away from the porous current collector 10. The negative electrode plate includes a porous current collector 10, a carbon material layer 20 and a non-conductive protective layer 30 stacked in sequence, wherein the carbon material layer 20 and the non-conductive protective layer 30 can be arranged on at least one surface of the porous current collector 10 along the thickness direction, preferably on two surfaces of the porous current collector 10 along the thickness direction.
[0082] In some embodiments, the thickness of the non-conductive protective layer 30 is 1 μm to 10 μm. Optionally, in some embodiments, the thickness of the non-conductive protective layer 30 is 1 μm to 8 μm. Optionally, in some embodiments, the thickness of the non-conductive protective layer 30 is 1 μm to 5 μm. Exemplarily, the thickness of the non-conductive protective layer 30 can be 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, or a range consisting of any two of the above values.
[0083] By making the thickness of the non-conductive protective layer 30 within the above range, it is beneficial to manufacture thin and light negative electrode plates, thereby improving the energy density of the battery cell. It also helps to provide certain protection for lithium dendrites, improve the safety performance of the battery, and avoid problems such as increased costs and reduced protective effects caused by the non-conductive protective layer 30 being too thick or too thin.
[0084] In some embodiments, the non-conductive protection layer 30 is a ceramic layer or a silicon material layer.
[0085] Optionally, in some embodiments, the non-conductive protective layer 30 is a ceramic layer. The ceramic layer is any one of aluminum oxide, boehmite, zirconium oxide, magnesium zirconium oxide, silicon oxide or silicon nitride. For example, the ceramic layer can be an aluminum oxide layer, a boehmite layer, a zirconium oxide layer, a magnesium zirconium oxide layer, a silicon oxide layer, a silicon nitride layer, etc.; of course, in other embodiments, other types of ceramic materials can also be used, which will not be repeated here.
[0086] In some embodiments, the particle size of the ceramic in the ceramic layer is 2 μm to 7 μm. Optionally, in some embodiments, the particle size of the ceramic in the ceramic layer is 1 μm to 6 μm. Optionally, in some embodiments, the particle size of the ceramic in the ceramic layer is 3 μm to 5 μm. Exemplarily, the particle size of the ceramic can be 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, or a range consisting of any two of the above values.
[0087] In this embodiment, a carbon material layer 20 is provided on the surface of the porous current collector 10, such as at least one carbon material layer 20 is provided on the surface of the copper foam or the modified copper foam, and the voids in the copper foam or the modified copper foam can be used as a space for lithium deposition, thereby reducing or avoiding the deposition of lithium dendrites on the surface, thereby reducing the length of lithium dendrites or eliminating lithium dendrites; the carbon material layer 20 can improve the conductivity of the negative electrode plate, and the carbon material layer 20 can also adsorb electrolyte, thereby improving the liquid retention of the battery cell, and can reduce the deposition of lithium ions on the surface of the plate due to lack of electrolyte; there are certain voids in the carbon material layer 20, which can be used as a space for lithium ion deposition, thereby reducing the deposition of lithium ions on the surface of the carbon layer; the carbon material layer 20 has a certain thickness, which can provide certain protection for lithium dendrites on the surface of the current collector. Further, a ceramic layer is provided on the surface of the carbon material layer 20 to provide a protective layer for lithium dendrites to prevent lithium dendrites from piercing the diaphragm.
[0088] Optionally, a small amount of adhesive may be provided in the ceramic layer, and this embodiment does not limit the specific type of the adhesive.
[0089] Optionally, in some embodiments, the non-conductive protective layer 30 is a silicon material layer. The silicon material layer is any one of silicon single substance, silicon alloy, silicon oxygen material or silicon nitrogen material. For example, the silicon material layer can be a silicon single substance layer, a silicon alloy layer, a silicon oxygen material layer such as a silicon oxide layer, a silicon nitrogen material layer, etc.
[0090] Optionally, the thickness of the silicon material layer is 1 μm to 5 μm.
[0091] The silicon material layer can provide a deposition space for lithium ions, and the non-lithium embedded area can be used as a semiconductor to prevent lithium dendrites from piercing the diaphragm and causing a short circuit. The silicon material layer within the above thickness range can provide protection for lithium dendrites while reducing the impact on battery energy density.
[0092] In this embodiment, a carbon material layer 20 is arranged on the surface of the porous current collector 10, such as at least one porous conductive carbon layer is arranged on the surface of the copper foam or modified copper foam, and at least one silicon material layer, such as a silicon layer or a SiO layer, is arranged on the surface of the porous conductive carbon layer. Among them, the porous conductive carbon layer can increase the active sites for the deposition of lithium ions on the surface of the negative electrode. In addition, the pores of the porous conductive carbon layer can provide space for the deposition of lithium ions and reduce the length of lithium dendrites; further, the silicon layer or silicon oxide layer deposited on the surface of the porous carbon layer, on the one hand, the part in contact with the porous carbon layer can participate in the reaction of lithium ions, thereby reducing the length of lithium ion dendrites. The silicon material layer such as the silicon layer or the SiO layer away from the conductive carbon layer can also be regarded as a non-conductive ceramic layer, which provides certain protection for lithium dendrites, thereby improving the safety performance of the negative electrode-free battery.
[0093] Optionally, in some embodiments, the silicon material layer may be a vapor-deposited silicon material layer, that is, the silicon material is deposited on the surface of the carbon material layer 20 by vapor deposition, thereby forming a silicon material layer on the surface of the carbon material.
[0094] When the silicon material layer is a vapor-deposited silicon material layer, as an example, the vapor-deposited silicon material layer is formed by adopting the vapor deposition technology in the prior art, for example, the silicon source for vapor deposition is one or more of silane, trichlorosilane, silicon tetrachloride, methyltrichlorosilane, methylchlorosilane, chloroethylsilane, dichlorodimethylsilane, dichlorodiethylsilane, methylsilane, dimethylsilane, trimethylsilane, tetramethylsilane, methyldisilane, dimethyldisilane, trimethyldisilane, tetramethyldisilane or hexamethylsilane. The process of vapor-deposited silicon source includes: heating to 1000°C at 5°C / min, respectively introducing high-purity nitrogen at a rate of 4.0L / min and silicon source gas at a rate of 0.5L / min, the mixed gas time is 8h, and naturally cooled to room temperature. Optionally, the vapor deposition equipment is a CVD equipment.
[0095] In some embodiments, the present application provides a battery, comprising: a positive electrode plate, a negative electrode plate as described above, and an electrolyte.
[0096] The battery provided in the present application is a negative electrode-free battery, and compared with conventional lithium-ion batteries or sodium-ion batteries using carbon materials or silicon materials as negative electrode active materials, the energy density of the battery can be greatly improved.
[0097] The battery provided in the present application adopts the negative electrode plate provided in the present application, which can induce uniform lithium deposition, reduce or avoid lithium dendrites, reduce the length of lithium dendrites, provide protection for lithium dendrites, improve the safety performance of the battery, and also improve the cycle performance of the battery.
[0098] In some embodiments, the battery further includes a separator, which is disposed between the positive electrode plate and the negative electrode plate and mainly serves to prevent the positive and negative electrodes from short-circuiting while allowing ions to pass through.
[0099] In this embodiment, the material and shape of the isolation membrane are not particularly limited, and it can be any technology disclosed in the prior art. The present application has no particular restrictions on the type of isolation membrane, and any known porous structure isolation membrane with good chemical stability and mechanical stability can be selected. As an example, the isolation membrane can be selected from one or more of glass fiber, non-woven fabric, polyethylene, polypropylene, polyvinylidene fluoride, etc.
[0100] The electrolyte mentioned above may be a solid electrolyte or a liquid electrolyte.
[0101] Optionally, when the electrolyte is a liquid electrolyte, that is, an electrolyte, the electrolyte is composed of a solvent, a lithium salt, and an optional additive. The electrolyte that can be used in the embodiments of the present application can be an electrolyte known in the prior art. The specific type and structure of the electrolyte can be an electrolyte type that can be used for a battery as is known in the art, such as an ester electrolyte or an ether electrolyte, etc., which is not limited and will not be repeated here.
[0102] In some embodiments, the positive electrode sheet includes a positive electrode current collector and a positive electrode material layer disposed on the positive electrode current collector.
[0103] In this embodiment, the specific materials and structures of the positive electrode current collector and the positive electrode material layer in the positive electrode plate are not limited, and the positive electrode plate structure and components that are well known in the art and can be used for batteries can be selected.
[0104] As an example, the positive electrode material layer includes a positive electrode active material, and the positive electrode active material contains lithium. When charging, the lithium element can be released to form lithium ions, and migrate to the negative electrode plate through the electrolyte to be reduced to metallic lithium. The embodiment of the present application does not limit the type and composition of the positive electrode active material, as long as the above principles are met. For example, it can be a lithium battery positive electrode active material, such as lithium cobalt oxide, lithium manganese oxide, lithium iron phosphate, nickel cobalt manganese oxide (NCM), nickel cobalt aluminum oxide, etc.
[0105] In some embodiments, the battery may further include a packaging shell, i.e., a shell, which encapsulates a positive electrode sheet, a separator, a negative electrode sheet, and an electrolyte, as well as other components known in the art in the battery, and this application does not limit the above-mentioned other components. This application does not specifically limit the packaging shell, and it can be a packaging shell known in the art, as long as it can achieve the purpose of this application.
[0106] In this embodiment, the battery can be prepared into batteries of different structures according to the situation, and there is no special limitation. As an example, the battery structure of the present application includes but is not limited to soft-pack batteries, square hard-shell batteries or cylindrical hard-shell batteries. That is, the battery can be cylindrical, flat, rectangular or other shapes.
[0107] The present invention is further described below in conjunction with specific embodiments. The implementation methods described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application.
[0108] Example 1
[0109] 1. Negative electrode
[0110] The negative electrode sheet includes a porous current collector 10 and a carbon material layer 20 disposed on both surfaces of the porous current collector 10 in the thickness direction;
[0111] Among them, 15 μm thick copper foam is used as the porous current collector 10; using vapor deposition technology (as an example, the process of vapor deposition includes: placing the porous current collector in a reactor, introducing a protective gas, heating to 400-1000°C at 1-5°C / min, introducing an organic carbon source gas at a rate of 0.5-20.0L / min, keeping the temperature for 0.5-20h, and naturally cooling to room temperature to obtain a vapor-coated product, that is, a carbon material layer. Among them, there are The organic carbon source can be one or more of methane, ethane, propane, isopropane, butane, isobutane, ethylene, propylene, acetylene, butylene, vinyl chloride, vinyl fluoride, difluoroethylene, ethyl chloride, fluoroethane, difluoroethane, methyl chloride, fluoromethane, difluoromethane, trifluoromethane, methylamine, formaldehyde, benzene, toluene, xylene, styrene, and phenol. A carbon material layer 20 is deposited on the surface and inside of the copper foam. The carbon material layer 20 is a porous carbon layer with a thickness of 1 μm. The porosity of the carbon material layer 20 is 40%, and the porosity of the porous current collector 10 is 50%.
[0112] 2. Positive electrode
[0113] The positive electrode sheet includes a positive electrode collector and a positive electrode material layer disposed on both surfaces of the positive electrode collector in a thickness direction.
[0114] Among them, aluminum foil or composite aluminum foil is used as the positive electrode current collector; the positive electrode material layer includes a positive electrode active material, a conductive agent and a binder; the positive electrode active material is a ternary high-nickel material, the conductive agent is one or more of SP, CNTs, and graphene; the binder is PVDF, etc.
[0115] For example, the positive electrode active material is NCM high nickel material, the chemical formula is LiNi 0.8 Co 0.1 Mn 0.1 O2 The conductive agent is CNTs, and the binder is PVDF; the mass ratio of the positive electrode active material, the conductive agent and the binder is 98:1:1.
[0116] The batching process uses existing technology to evenly mix the main positive electrode active material, conductive agent, adhesive and other materials and solvent NMP, and then apply them on the positive electrode collector. The coating can be applied by transfer or extrusion, and then after drying and cold pressing, the positive electrode sheet is obtained, with a compaction density of 3.3-3.6 g / cm 3 (Compacted density 3.4g / cm 3 ).
[0117] 3. The isolation membrane can be made of polyethylene film, polypropylene film, polyvinylidene fluoride film and non-woven fabric.
[0118] For example, the separator film is selected from polyethylene film.
[0119] 4. The electrolyte includes a lithium salt and a solvent. The types of the lithium salt and the solvent are not specifically limited and can be selected according to actual needs. For example, the lithium salt can be LiPF 6 、LiTFSI、LiBF 4 wait.
[0120] For example, LiPF is used as electrolyte 6 Dissolved in a solvent of ethylene carbonate, ethyl methyl carbonate and diethyl carbonate in a ratio of 1:1:1, with a concentration of 1.2 mol / L.
[0121] 5. Battery
[0122] During the cell assembly process, the positive electrode sheet, the separator, and the negative electrode sheet are arranged in sequence by winding. The electrolyte is injected into the dry cell, and a lithium battery is obtained after formation and aging.
[0123] Example 2
[0124] The main difference between Example 2 and Example 1 is:
[0125] In the negative electrode sheet, the thickness of the carbon material layer 20 is 2 μm.
[0126] The rest are the same as in Example 1.
[0127] Example 3
[0128] The main difference between Example 3 and Example 1 is:
[0129] In the negative electrode sheet, the thickness of the carbon material layer 20 is 3 μm.
[0130] The rest are the same as in Example 1.
[0131] Example 4
[0132] The main difference between Example 4 and Example 1 is:
[0133] In the negative electrode sheet, the porosity of the carbon material layer 20 is 60%, and the porosity of the porous current collector 10 is 80%.
[0134] The rest are the same as in Example 1.
[0135] Example 5
[0136] The main difference between Example 5 and Example 1 is:
[0137] In the negative electrode sheet, the porosity of the carbon material layer 20 is 20%, and the porosity of the porous current collector 10 is 10%.
[0138] The rest are the same as in Example 1.
[0139] Example 6
[0140] The main difference between Example 6 and Example 1 is:
[0141] The negative electrode sheet includes a porous current collector 10, a carbon material layer 20 disposed on two surfaces of the porous current collector 10 in the thickness direction, and a silicon material layer disposed on the surface of the carbon material layer 20;
[0142] Among them, 15μm thick foam copper is used as the porous current collector 10; the porosity of the porous current collector 10 is 50%; the carbon material layer 20 is a porous carbon layer, the thickness of the carbon material layer 20 is 1μm, and the porosity of the carbon material layer 20 is 40%; a silicon material layer is deposited on the carbon material using vapor deposition technology, and the thickness of the silicon material layer is 1μm.
[0143] The rest are the same as in Example 1.
[0144] Example 7
[0145] The main difference between Example 7 and Example 6 is:
[0146] In the negative electrode sheet, the thickness of the silicon material layer is 3 μm.
[0147] The rest are the same as in Example 6.
[0148] Example 8
[0149] The main difference between Example 8 and Example 6 is:
[0150] In the negative electrode sheet, the thickness of the carbon material layer 20 is 5 μm.
[0151] The rest are the same as in Example 6.
[0152] Example 9
[0153] The main difference between Example 9 and Example 1 is:
[0154] The negative electrode sheet includes a porous current collector 10, a carbon material layer 20 disposed on two surfaces of the porous current collector 10 in the thickness direction, and a ceramic layer disposed on the surface of the carbon material layer 20;
[0155] Among them, 15μm thick foam copper is used as the porous current collector 10; the porosity of the porous current collector 10 is 50%; the carbon material layer 20 is a porous carbon layer, the thickness of the carbon material layer 20 is 1μm, and the porosity of the carbon material layer 20 is 40%; the thickness of the ceramic layer is 2μm.
[0156] The rest are the same as in Example 1.
[0157] Example 10
[0158] The main difference between Example 10 and Example 9 is:
[0159] In the negative electrode sheet, the thickness of the ceramic layer is 4 μm.
[0160] The rest is the same as Example 9.
[0161] Embodiment 11
[0162] The main difference between Example 11 and Example 9 is:
[0163] In the negative electrode sheet, the thickness of the ceramic layer is 7 μm.
[0164] The rest is the same as Example 9.
[0165] Comparative Example 1
[0166] The main difference between Comparative Example 1 and Example 1 is:
[0167] In the negative electrode sheet, a common copper foil is used as the current collector (negative electrode sheet), and the thickness of the copper foil is 6 μm.
[0168] The rest are the same as in Example 1.
[0169] Comparative Example 2
[0170] The main difference between Comparative Example 2 and Example 1 is:
[0171] In the negative electrode sheet, foam copper is used as the current collector (negative electrode sheet), the thickness of the foam copper is 15 μm, and the porosity of the foam copper is 50%.
[0172] The rest are the same as in Example 1.
[0173] Performance Testing
[0174] (1) Lithium dendrite length: Take a battery whose capacity has decayed to 80% of its initial capacity, disassemble it, cut the end face of the electrode, and measure the length of the lithium dendrite under an electron microscope (CP test).
[0175] (2) Cycle life test: 25°C, using a battery charge and discharge tester, 1 / 3C constant current charging to 4.25V, constant voltage charging to a cut-off current of 0.05C; let stand for 30 minutes, 1 / 3C constant current discharge to 3V. The cycle life is the number of cycles for the discharge capacity to decay to 80% of the initial capacity.
[0176] (3) Energy density test: At 25°C, use a battery charge and discharge tester, charge at 1 / 3C constant current to 4.25V, and charge at constant voltage to a cut-off current of 0.05C; let stand for 30 minutes, discharge at 1 / 3C constant current to 3V, and record the discharge energy. Energy density = discharged energy / cell weight.
[0177] The test results are shown in Table 1 below.
[0178] Table 1
[0179] Group Lithium dendrite length (μm) Cycle life (number of turns) Energy density (Wh / kg) Example 1 35 100 352 Example 2 30 150 349 Example 3 25 200 345 Example 4 31 120 354 Example 5 37 90 350 Example 6 16 230 345 Example 7 12 245 339 Example 8 5 255 329 Example 9 18 215 320 Example 10 11 235 315 Embodiment 11 6 245 310 Comparative Example 1 50 50 360 Comparative Example 2 40 80 355
[0180] It can be seen from the data in Table 1 that the negative electrode plate provided in the embodiment of the present application can reduce the length of lithium dendrites and improve the safety performance and cycle life of the battery.
[0181] The parts of the present invention that are not described in detail are well known to those skilled in the art.
[0182] The basic principle of the present invention is described above in conjunction with specific embodiments. However, it should be pointed out that the advantages, strengths, effects, etc. mentioned in the present invention are only examples and not limitations, and it cannot be considered that these advantages, strengths, effects, etc. are required by each embodiment of the present invention. In addition, the specific details disclosed above are only for the purpose of illustration and ease of understanding, not limitation, and the above details do not limit the present invention to being implemented by adopting the above specific details.
[0183] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the utility model, rather than to limit it. Although the utility model has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the various embodiments of the utility model.
Claims
1. A negative electrode plate, characterized in that: The negative electrode plate comprises: porous current collector; a carbon material layer, the carbon material layer being disposed on at least one surface of the porous current collector in a thickness direction; Wherein, the porosity of the carbon material layer is 20% to 70%, and the porosity of the porous current collector is 10% to 90%.
2. The negative electrode sheet according to claim 1, characterized in that: The porous current collector includes one of foamed copper or modified foamed copper.
3. The negative electrode sheet according to claim 1, characterized in that: The pore size of the porous current collector is 0.05 mm to 5 mm; The thickness of the porous current collector is 5 μm to 50 μm.
4. The negative electrode sheet according to claim 1, characterized in that: The carbon material layer is a porous carbon layer, and the porous carbon layer is any one of carbon nanospheres, carbon nanotubes, carbon nanosheets or three-dimensional nanocarbon materials; The pores of the porous carbon layer have a pore size of 0.6 nm to 4 nm.
5. The negative electrode sheet according to claim 1, characterized in that: The carbon material layer is a common carbon material layer, and the common carbon material layer is any one of graphene, conductive carbon black, activated carbon or carbon nanotubes.
6. The negative electrode sheet according to claim 1, characterized in that: The thickness of the carbon material layer is 1 μm to 10 μm.
7. The negative electrode sheet according to any one of claims 1 to 6, characterized in that: The negative electrode plate further includes a non-conductive protective layer, which is disposed on a surface of the carbon material layer on a side away from the porous current collector.
8. The negative electrode sheet according to claim 7, characterized in that: The thickness of the non-conductive protective layer is 1 μm to 10 μm.
9. The negative electrode sheet according to claim 7, characterized in that: The non-conductive protective layer is a ceramic layer or a silicon material layer; Wherein, the ceramic layer is any one of aluminum oxide, boehmite, zirconium oxide, magnesium zirconium oxide, silicon oxide or silicon nitride; The particle size of the ceramic in the ceramic layer is 2 μm to 7 μm; The silicon material layer is any one of silicon single substance, silicon alloy, silicon oxygen material or silicon nitrogen material.
10. A battery, characterized in that: The battery comprises: A positive electrode sheet, a negative electrode sheet as claimed in any one of claims 1 to 9, and an electrolyte.